A surface-tunnel frequency domain electromagnetic method for mineral exploration in Tajikistan area - Wang, Hongyu; Liu, Jianxin; Guo, Wenbo; Tian, Shengqi (Frontiers in Energy Research, 2023)
For old mines, numerous mining tunnels exist, which can potentially bring us closer to the deep ore-bearing structures. Therefore, we propose a surface-tunnel frequency domain electromagnetic (EM) method to utilize these mining tunnels for geophysical exploration. In this method, the transmitter is placed on the Earth's surface, while the receiver is positioned within the tunnel space, providing higher resolution due to its proximity to the target body. This paper presents the derived analytical solution for the electric field in the surface-tunnel configuration. We also propose a survey system for our surface-tunnel frequency domain electromagnetic method and provide a field example of lead-zinc deposits in Tajikistan. Synthetic cases demonstrate a significant enhancement of the EM signal when the receiver is moved into the tunnel. The field application validates the practicality of our surface-tunnel frequency domain EM method for deep mineral exploration in active mines.